Salvage of a Near-Total Penile Amputation following Urinary Fistulization and Carbapenemase-Producing Klebsiella pneumoniae Infection with a Composite ALT Flap and Vascularized Fascia Lata - Horta, Ricardo; Mendes, Margarida; Barreiro, Diogo; Almeida, Alexandre; Jarnalo, Mariana; Teixeira, Sérgio; Pinto, Rui (The Surgery Journal, 2021)
Reconstruction of complex penile defects is always challenging, as some defects are not possible to reconstruct with skin or mucosa grafts, and even local flaps may be precluded in complex wounds. We present a case of a 63-year-old otherwise healthy man, who underwent transurethral resection of the prostate for benign prostatic hyperplasia. After the procedure, he developed panurethral necrosis with consequent stricture. Three urethroplasties for reconstruction of the bulbar and distal urethra using buccal mucosa grafts, a preputial flap, and penile skin were performed by urology team in different institutions, but serious urinary fistulization and carbapenemase-producing Klebsiella pneumoniae (KPC) infection translated in a chronic wound, urethra necrosis, and near-total penile amputation. A composite anterolateral thigh flap and vascularized fascia lata were used with success together with a perineal urethroplasty in different stages, improving the ischemic wound condition. The extended segment of fascia lata was used for Buck's fascia replacement and circumferential reinforcement to cover the erectile bodies of the penis. The postoperative period was uneventful and after 12 months, there were no signs of recurrence or wound dehiscence. He was able and easily adapted to void in a seated position through the perineal urethrostomy that was made. To the best of our knowledge, this procedure has not been reported previously as a salvage procedure in a fistulizated and KPC infected penis, but it may be considered to avoid penile amputation in chronic infected and intractable wounds.
Keywords: penile amputation; salvage; KPC infection; ALT flap; vascularized fascia lata